Assessment of Visual Quality in Eyes with Forme Fruste Keratoconus and Mild and Moderate Keratoconus Based on Optical Quality Analysis System II Parameters - Zhonghao Ren; Liyan Xu; Qi Fan; Kaili Yang; Shengwei Ren; Dongqing Zhao (Journal of Ophthalmology)
Purpose. The study aimed to evaluate the visual quality of forme fruste keratoconus (FFK) and mild and moderate keratoconus by using an optical quality analysis system II (OQAS-II) and to explore the correlation between optical quality parameters and the disease progression. Methods. Twenty-one normal eyes, twenty-one FFK eyes, twenty-one mild keratoconus eyes, and twenty-one moderate keratoconus eyes were included in this prospective study. The optical quality parameters, such as object scatter index (OSI), modulation transfer function cutoff (MTF cutoff), strehl ratio (SR), and OQAS-II values at contrasts of 100% (OV-100), 20% (OV-20), and 9% (OV-9), were measured by OQAS-II. The repeatability of these parameters was analyzed by intraclass correlation coefficient (ICC), repeatability coefficient (RC), and coefficient of variation (CVw). Correlations between optical quality parameters and mean central keratometry readings (Kmean) were evaluated. The sensitivity and specificity of the parameters were analyzed using the receiver operating characteristic (ROC). Results. All the optical quality parameters among four groups showed good repeatability (all ICC≥0.75). The MTF cutoff, SR, OV-100, OV-20, OV-9 in FFK, mild and moderate keratoconus eyes were significantly lower than those in the normal group (all P<0.05). The ROC analyses of the MTF cutoff, SR, OV-100, OV-20, and OV-9 showed significant area under the curve (AUC) in discriminating FFK form normal, mild keratoconus from FFK, and moderate keratoconus from mild keratoconus (all P<0.05). The OSI in mild and moderate keratoconus eyes were significantly higher than that in FFK and normal group (all P<0.05), while the OSI showed no significant difference between the FFK group and normal group (P>0.05). The ROC analyses of the OSI showed significant AUC in discriminating mild keratoconus from FFK and moderate keratoconus from mild keratoconus (all P<0.05). In addition, the MTF cutoff was closely correlated to Kmean in keratoconus eyes (r = −0.710, P<0.001). Conclusion. The repeatability of OQAS-II is good in measuring visual quality of normal as well as FFK, mild, and moderate keratoconus. The visual quality of the FFK, mild, and moderate keratoconus is worse than that in normal eyes. The OQAS-II has the potential value in screening FFK from normal eyes and might be a useful tool for evaluating the progression of keratoconus.